Histopathological Effects of Cadmium Chloride on the Kidney in Japanese Quail - Mohammed, Hind A.; Taha, Ameer M. (International Journal of Scientific Research in Biological Sciences, 2021)
Cadmium is one of the most dangerous heavy metals for its long life and its acute and chronic effects. The current study aims to identify the effect of exposure to cadmium chloride on the histological structure of the kidneys in one of the Japanese quail, Coturnix coturnix japonica. The study included two groups, a control group, and an experimental group. The birds of the experimental group were dosed to a concentration of 50mg/kg for four continuous days. The birds were sacrificed 4,15,30,60 days after the start of the experiment. The results of the histological examination of the kidney showed the emergence of many lesions in the four periods, to varying degrees between them. Among the most prominent of these is the appearance of the emergence of hydropic degeneration, necrosis, and desquamation in the renal tubules. Deformation, irregularity, and dilaceration of some glomeruli and atrophy of others were observed, expanding Bowman`s space. The study concluded that the cadmium chloride causes much tissue damage to the body of the quail bird and that it is necessary to take into account not to be exposed to this element to maintain its economic value.